A new species of Eigenmannia Jordan & Evermann (Teleostei: Gymnotiformes: Sternopygidae) from Río Ventuari, Venezuela - Dutra, Guilherme Moreira; Peixoto, Luiz Antônio Wanderley; Santana, Carlos David De; Wosiacki, Wolmar Benjamin (Zootaxa, 2018)
A new species of Eigenmannia is described from the Río Ventuari, Río Orinoco basin, Venezuela. It is distinguished from congeners by the presence of a bony dorsolateral flange on the dentary, the presence of teeth attached along a bony dorsolateral flange, and by the first premaxillary teeth attached to the anteroventral margin of the premaxilla. It is further distinguished from all remain congeners by a combination of characters, including a subterminal mouth, 99–107 scales along the lateral line until the end of the anal fin, and ii, 16–17 pectoral-fin rays.